Synthesis and Antibacterial Activity of PEG Polycyclic Acetal Metal Complex/ PVA Polymer Blend Film - Younus, Maha A.; Ali, Media Umran (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2020)
Polyacetal was synthesized from the reaction of Polyethylene glycol with4- dimethylaminobenzaldehyde.Polymer metal complex was synthesized by the reaction with Ag+; polymer blend with polyvinyl alcohol was synthesized solution casting technique. All synthesized compounds were characterized by FT-IR in addition to the antimicrobial activity. The FT-IR spectra indicate the formation of the polyacetal. The DSC resultsindicatethe thermal stability regarding the synthesized polymer blends. The synthesized polyacetal, its metal complex and PA blend against four types of bacteria (gram+ve) Staphylococcus aureas, Bacillus subtilis and (gram –ve)Klebsiella pneumoniae, Escherichia Coli were evaluated. The results revealed that the polyacetal-Ag complex has the greater potential against all kinds of bacteria than polyacetal and polymer blend.